Efektifitas Rezim Non-proliferasi Nuklir Global: Teorisasi dan Implementasi - I Gede Wagyu Wicaksana (Department of International Relations, Brawijaya University, 2014)
Abstract Expansion and proliferation of nuclear weapons have become an international issue since World War II, with their serious implications to peace and security. International efforts to restrict and eliminate nuclear weapons undergo ups and downs. The Non-Proliferation Treaty, however, is widely considered to have worked out well in decreasing the prospects for further nuclearization. This article looks in detail at what the norm is effective in achieving the goal of global denuclearization. It presents theoretical and case-based analysis to show determining factors ofstates’ decisions to abandon nuclear weapon programs. Perspectif of strategic realism, liberal institutionalism and constructivism are canvassed to search for policy explanation. Keywords: denuclearization, NPT, nuclear weapons